A Systematic Review of Contralateral C7 Transfer for the Treatment of Traumatic Brachial Plexus Injury: Part 1. Overall Outcomes - Yang, Guang; Chang, Kate W-C; Chung, Kevin C (Plastic and reconstructive surgery (1963), 2015)
Contralateral C7 (CC7) transfer has been used for treating traumatic brachial plexus injury. However, the effectiveness of the procedure remains a subject of debate. The authors performed a systematic review to study the overall outcomes of CC7 transfer to different recipient nerves in traumatic brachial plexus injuries. A literature search was conducted using PubMed and EMBASE databases to identify original articles related to CC7 transfer for traumatic brachial plexus injury. The data extracted were study/patient characteristics, and objective outcomes of CC7 transfer to the recipient nerves. The authors normalized outcome measures into a Medical Research Council-based (MRC) outcome scale. Thirty-nine studies were identified. The outcomes were categorized based on the major recipient nerves: median, musculocutaneous, and radial/triceps. Regarding overall functional recovery, 11 percent of patients achieved MRC grade M4 wrist flexion and 38 percent achieved MRC grade M3. Grade M4 finger flexion was achieved by 7 percent of patients, whereas 36 percent achieved M3. Finally, 56 percent achieved greater than or equal to S3 sensory recovery in the median nerve territories. In the musculocutaneous nerve group, 38 percent regained to M4 and 37 percent regained to M3. In the radial/triceps nerve group, 25 percent regained elbow or wrist extension strength to a MRC grade M4 and to M3, respectively. Outcome measures in the included studies were not consistently reported to uncover true patient-related benefits from the CC7 transfer. Reliable and validated outcome instruments should be applied to critically evaluate patients undergoing CC7 transfer.